Similarity-based pattern recognition : Third International Workshop, SIMBAD 2015, Copenhagen, Denmark, October 12-14, 2015 Proceedings /: Third International Workshop, SIMBAD 2015, Copenhagen, Denmark, October 12-14, 2015 Proceedings. (2015) - Unknown
No abstract available